Mechanochemically synthesised dicyanamide hybrid organic–inorganic perovskites, and their melt-quenched glasses. Issue 24 (4th March 2022) - McHugh, Lauren N.; Thorne, Michael F.; Chester, Ashleigh M.; Etter, Martin; Užarević, Krunoslav; Bennett, Thomas D.
Abstract : Dicyanamide hybrid organic–inorganic perovskites were synthesised mechanochemically and their properties, along with those of their bulk melt-quenched glasses were investigated. Abstract : Here we present efficient and scalable mechanochemical formation of hybrid organic–inorganic perovskites of the form [TPrA][M(dca)3 ] (M = Mn 2+, Co 2+ ) and the subsequent formation of their bulk melt-quenched glasses. In situ X-ray diffraction reveals direct, facile, and almost instantaneouos formation of both crystalline materials, while slow cooling limits recrystallisation in glasses. The glasses show good stability to acidic and basic aqueous solutions and display higher carbon dioxide uptakes than their crystalline precursors.